Religious participation and civil society: the case of post-communist countries - Salnikova, Svitlana; Myronovych, Dmytro (Ukrainian Sociological Journal, 2015)
Features of the relationship between religion and civil society – namely, how the level of religious participation correlates with the level of civic activity in societies with dominance of different religious traditions – are considered in the article. The authors note that the consideration of the relationship between religion and civil society in post-communist countries is problematized by state of this society – the absence or underdevelopment of civil institutions, low levels of interpersonal trust and social capital, lack of motivation. According to the traditions of social capital study authors note that exactly membership in religious organizations played an important role in the formation of civic space and formation of institutions of civil society in countries of Europe and the USA.